Rarer Clinical Associations of Antiphospholipid Antibodies - Gillis, David; Wong, Richard C.W. (Seminars in Thrombosis and Hemostasis, 2012)
Detection of antiphospholipid antibodies (aPL) are central to the definition of the antiphospholipid (antibody) syndrome (APS). Thrombosis in certain vascular beds, such as the cerebral circulation, the veins of the lower legs and cutaneous vessels, and/or fetal loss, are common manifestations of APS. However, aPL have been found in association with a large range of other clinical conditions—these conditions constitute a rather heterogeneous group and are the subject of this review. Thus, aPL may rarely be found in association with thromboses of vascular beds other than those commonly associated with APS. The combination of thrombosis and aPL still satisfies the criteria for APS, and management of this group of patients is the same as that of APS associated with the more common manifestations of the disease. Alternatively, aPL may be detected in a range of conditions where thrombosis cannot be clearly demonstrated, such as duodenal ulcer or transverse myelopathy. The approach to management of patients who have aPL in association with these conditions is less clear, although in some cases interventions to remove the associated antibody have been associated with amelioration of the condition. Finally, in several studies, aPL have been detected in a proportion of patients with conditions occurring commonly in the normal population—these findings have to be treated with caution in view of inconsistent findings between the reported results and methodological limitation of studies purporting to show positive results.
Keywords: antiphospholipid antibodies; antiphospholipid syndrome; thrombosis; rare associations